Ensuring consideration of water quality in nexus approaches in the science–practice continuum: reply to discussion of "Water quality: the missing dimension of water in the water–energy–food nexus?". Issue 8 (11th June 2022) - Heal, K. V.; Bartosova, A.; Hipsey, M. R.; Chen, X.; Buytaert, W.; Li, H.-Y.; McGrane, S. J.; Gupta, A. B.; Cudennec, C.
ABSTRACT: We thank Arnbjerg-Nielsen and co-authors for their constructive contribution. We endorse their key comments and suggestions on how to increase awareness of and action on water quality interactions in the water–energy–food (WEF) nexus. Here, we advance the discussion, commenting on the scope of water quality to embrace ecosystem as well as human needs, and the importance of transdisciplinarity and focusing at the city/aquifer/drainage basin scale in WEF nexus hotspots in ensuring that water quality is considered in WEF nexus approaches. We also identify how recent global events, the COVID-19 pandemic and the 26th Conference of the Parties to the UN Framework Convention on Climate Change (UNFCCC COP 26), may intensify the WEF nexus and its water quality interlinkages, highlighting the need to weave WEF considerations into addressing the United Nations Sustainable Development Goals and the climate and biodiversity emergencies.